2019
DOI: 10.1103/physreva.99.062709
|View full text |Cite
|
Sign up to set email alerts
|

Experimental electron-detachment cross sections for collisions of O2 with N2 molecules in the energy range 50–7000 eV

Abstract: Experimental electron-detachment cross sections for collisions of Experimental electron-detachment cross sections for collisions of O2-with N2 Experimental electron-detachment cross sections for collisions of O2-with N2 molecules in the energy range 50-7000 eV molecules in the energy range 50-7000 eV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…As to the authors' knowledge, no previous experimental or theoretical TEDCS data have been reported in the literature. If we compare these results with our recent measurements for O 2 − collisions with N 2 [17], we see that the average magnitude of the TEDCS in the common energy range (50-1000 eV) is in concordance with their respective molecular masses, i.e., 3-4 times higher for benzene than for nitrogen. In addition, the energy dependence of the TEDCSs shows some similarities for both molecular targets.…”
Section: Total Electron Detachment Cross Sectionssupporting
confidence: 71%
See 4 more Smart Citations
“…As to the authors' knowledge, no previous experimental or theoretical TEDCS data have been reported in the literature. If we compare these results with our recent measurements for O 2 − collisions with N 2 [17], we see that the average magnitude of the TEDCS in the common energy range (50-1000 eV) is in concordance with their respective molecular masses, i.e., 3-4 times higher for benzene than for nitrogen. In addition, the energy dependence of the TEDCSs shows some similarities for both molecular targets.…”
Section: Total Electron Detachment Cross Sectionssupporting
confidence: 71%
“…For N 2 , a prominent local maximum is shown around 200 eV (see Ref. [17]), while for benzene, two local maxima at 40 and 400 eV and a minimum around 320 eV are discernible. In contrast with nitrogen, these features are not well defined for benzene, and their respective magnitudes follow the flat tendency of the TEDCS if we consider their total uncertainty limits.…”
Section: Total Electron Detachment Cross Sectionsmentioning
confidence: 94%
See 3 more Smart Citations